'So nobly struggling for their manhood': masculinity and violence among steelworkers in the wheeling district, 1880–1910. (3rd September 2019) - Martin, Lou
ABSTRACT: Between 1880 and 1910, new technologies and managerial schemes undermined skilled steelworkers' ability to control production and demand high wages, which also threatened their sense of manhood. The steelworkers in the Wheeling District of northern West Virginia and eastern Ohio remained a union stronghold until the 1909–1910 steel strike. Steelworkers defined manhood in terms of their family wage, a manly bearing toward their bosses, solidarity with fellow workers, and their rights, all closely associated with union membership. Faced with the loss of their union, they turned to violence – not just out of frustration or to win the strike – but also to defend their rights and freedoms and reclaim their masculine identity.